Hurricane Dorian and COVID-19: a review of the consecutive disasters in the Bahamas - Sankam, Joshitha (International Journal Of Community Medicine And Public Health, 2020)
The Bahamas are an archipelago of islands north of Cuba and east of Florida, home to around 400,000 people. The Bahamas was hit by Hurricane Dorian which made severe landfall at the end of 2019 and consequently by COVID-19 pandemic in early 2020. This paper provides an overview of Hurricane Dorian and COVID-19 in the Bahamas and a review of the impacts and consequences caused by the disasters on the livelihood, vulnerable population and economy of the Bahamas. Crippled by the double burden of a natural and a biological disaster that happened consecutively, the small island country needs to strengthen its strategic framework to build its preparedness and economy for future events.